UNVEILING THE CAUSES OF FINAL PROJECT FAILURE: A QUALITATIVE ANALYSIS AMONG DIPLOMA IV STUDENTS - Setiawan, Irwan; Diani, Fitri; Aditya, Yadhi (Sanata Dharma University Yogyakarta, 2025)
Completing final projects is a pivotal milestone for Diploma IV (Applied Bachelor) students. However, the incidence of project failure remains a concerning issue. Exploring the underlying factors contributing to this failure is crucial for devising effective interventions to bolster student success. Despite the significance of final projects, many students struggle to complete them. This research explores the root causes of final project failure among Diploma IV students, focusing on internal and external influences. This study used a qualitative approach to analyze survey data from 59 respondents undertaking their final projects. Using the Fishbone Diagram, the analysis uncovered a spectrum of factors contributing to project failure. These factors encompassed internal challenges such as time management and motivation, external issues including academic support and institutional policies, and personal factors such as mental health and coping abilities. Understanding these multifaceted factors provides valuable insights into the challenges faced by students and informs the development of targeted interventions to support their academic success.